Health Professionals' Attitude Toward the Use of Social Media for COVID-19 Related Information in Northwest Ethiopia: A Cross-Sectional Study - Tegegne, Masresha Derese; Endehabtu, Berhanu Fikadie; Guadie, Habtamu Alganeh; Yilma, Tesfahun Melese (Frontiers in Public Health, 2022)
Background: Social media platform is one way to share online information regarding pandemic prevention. However, there is no study regarding the attitude of health professionals on social media use for COVID-19 related information. This study aimed to assess health professionals’ attitudes toward using social media for COVID-19 related information. Method: An institution-based cross-sectional study was conducted among 355 health professionals in Bahir Dar city public health centers, Northwest Ethiopia. A pretested self-administered questionnaire was used to collect the data. The data were entered by EPI-data version 4.6 and analyzed using SPSS version 23 software. Descriptive statistics, bivariable and multivariable logistic regression analysis were done, and adjusted odds ratio and p-value were used to describe the outcome variable and to identify associated factors Result: Out of 341 participants, about 73% of the participants had good attitude towards use of social media for COVID-19 information. Age < 24 and 25-34 (AOR=3.74, 95% CI: [1.53-9.13]) and (AOR=2.25, 95% CI: [1.04-4.86]), computer training (AOR= 2.03, 95% CI: [1.03-4.00]), Usefulness of social media (AOR=3.25, 95% CI: [1.58-6.67]), and Trustworthiness (AOR=3.57, 95% CI: [1.93-6.60]) were enabling factors for attitude towards the use of social media for COVID-19 related information. Conclusion: Health professionals had a moderate attitude towards using social media for accessing COVID-19-related information. This implies that after considering positive attitude predictors, such as providing basic computer training, emphasising the usefulness of social media, and building trusted social media pages, social media platforms can be used as a source of COVID-19 related information for health professionals.